ENTREPRENEURIAL LEARNING IN THE CONTEXT OF FAILURE AND CREATION OF NEW BUSINESS - Dias, Tania Regina Frota Vasconcellos; Martens, Cristina Dai Prá; Lacerda, Fabrício Martins (Brazilian Creative Industries Journal, 2021)
This research aims to describe the career and the entrepreneurial learning of micro-enterprises owners that identified new opportunities after the business failure. The methodology consists of a qualitative and exploratory study, with a cross-section approach and longitudinal perspective. Two entrepreneurs participated in the study, selected by convenience and availability, based on established criteria. Data collection was conducted through in-depth interviews, the interviews were recorded and transcribed. The dates were analyzed using content analysis. The study shows that new knowledge emerged from a learning journey in the context of business failure. It is learning about yourself, persistence, and resilience to succeed in new activities; about business and failure, flexibility to change the focus; on networks and relationships, as experience working with partners, employees and establish a network with the business partners; and on business management, to learn to minimize risks, because they understand that you must have a minimum knowledge of the market. During the development of new business, there is a predominance of exploration to transform the experience into entrepreneurial knowledge.